Efektivitas Penggunaan Media Pembelajaran Berbasis ICT dan Kreativitas Belajar Siswa terhadap Hasil Belajar Ekonomi: Studi Eksperimen pada Siswa Kelas X SMA Negeri 64 Jakarta - Duta Ramadan; Agus Wibowo; Ari Saptono (Indo Publishing, 2026)
This study aims to examine the effectiveness of ICT-based learning media and student learning creativity on economic learning outcomes through an experimental study at grade X SMA Negeri 64 Jakarta. A quantitative approach with a quasi-experimental pretest-posttest control group design was employed. The sample consisted of 72 students selected using cluster sampling, divided into an experimental group (36 students) using ICT-based learning media and a control group (36 students) using conventional learning methods. Data were collected through creativity questionnaires and economic learning outcome tests, then analyzed using descriptive statistics, prerequisite tests, and two-way ANOVA. The results show that: (1) there is a significant difference in learning outcomes between students using ICT-based learning media and those using conventional methods (F = 206.164; p = 0.000), with the experimental group achieving higher scores (mean = 89.03) than the control group (mean = 75.56); (2) there is a significant difference in learning outcomes between students with high and low learning creativity (F = 34.071; p = 0.000); and (3) there is no significant interaction between ICT-based learning media and learning creativity on economic learning outcomes (F = 0.024; p = 0.876). The model explains 79.1% of the variation in learning outcomes. These findings indicate that ICT-based learning media effectively improve student learning outcomes and creativity plays a significant role in determining academic achievement.